2007
DOI: 10.1111/j.1740-1461.2007.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Income and Career Satisfaction in the Legal Profession: Survey Data from Indiana Law School Graduates

Abstract: This article presents data on graduates of a law school located at a large, midwestern public university. It presents responses to survey questions relating to various personal and job characteristics, including income from the practice of law and career satisfaction. It compares the responses across various demographic groups, including type of practice, gender, race, and ethnicity. We find that lawyers in large private law firms make more money than lawyers in small private practices, who, in turn, make more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Career longevity may be a related factor (Dau‐Schmidt and Mukhopadhaya, ). For example, one cohort analysis revealed that attorneys with 15 years of practice were more satisfied with their careers overall than attorneys just five years out of law school (Stake, Dau‐Schmidt, Mukhopadhay, ). We include a variable for the years since passing the bar as a control for experience…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Career longevity may be a related factor (Dau‐Schmidt and Mukhopadhaya, ). For example, one cohort analysis revealed that attorneys with 15 years of practice were more satisfied with their careers overall than attorneys just five years out of law school (Stake, Dau‐Schmidt, Mukhopadhay, ). We include a variable for the years since passing the bar as a control for experience…”
Section: Methodsmentioning
confidence: 99%
“…The available evidence is mixed. Overall, among all attorneys, career satisfaction is fairly high (Organ, ), and most work finds little to no gender or racial differences on questions about career satisfaction (Organ, ; Dinovitzer and Garth, ; Stake, Dau‐Schmidt, and Mukhopadhaya, ). However, a meta‐analysis of career satisfaction surveys found that one consistent trend was that more recent entrants into the profession report less satisfaction than more seasoned attorneys (Organ, ; Stake, Dau‐Schmidt, and Mukhopadhaya, ).…”
Section: Bias and Stereotyping In The Legal Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graduates in a position to choose may forego some income for greater job and family satisfaction. Stake et al (2007) found some evidence of such a tradeoff among graduates of Indiana University School of Law-Bloomington. We do not control for these potentially confounding factors.…”
Section: B Influence Of School Rank On Earnings Of Graduatesmentioning
confidence: 99%
“…Second, with the dramatic changes in the composition of lawyers due to the rapid and substantial influx of women and, to a lesser extent, minorities, researchers concentrated their attention on gender and race (Epstein 1983; Hagan and Kay 1995; Wilkins 1999). Third, the dramatic nature of these findings drew ever greater interest to these lines of demarcation: women and minorities consistently earn less (Hagan and Kay 1995; Dau‐Schmidt and Mukhopadhaya 1999; Dinovitzer, Reichman, and Sterling 2009; Stake et al. 2007; but see Lempert, Chambers, and Adams 2000), are more likely to be located outside of the lucrative large‐firm sector (Kornhauser and Revesz 1995; Hull and Nelson 2000; Dinovitzer et al.…”
Section: Introductionmentioning
confidence: 99%